A díá fún: aproximações à imaginação iorubá na linguagem do sistema de Ifá - Verdugo, Marcos Vinícius de Souza (2016)
The critique of the forms of production of knowledge enables us to understand other experiences of humanity in relation to the concrete reality of the world. And, at the same time, points to the decolonization of the language in which knowledge is produced. Attention is focused on what is said, on why it is said and, above all, how it is said about the African imaginations. In this way, we ve chosen to develop some approaches to the imagination present in Yoruba language of Ifá system, discussing which elements constitute both the apparatus of Ifá (material elements) as those of the Yoruba conceptual imaginary. In the dynamics of approaches, it is the word that particularizes men and women, the sound that determines the rhythm of life, the body that in its performance marks the dual Yoruba reality and, finally, the Yoruba world itself that determines the language and the universe of meanings of the Ifá system. The Ifá system is a set of Yoruba oral statements representing the totality of knowledge that was developed over the material and spiritual history of that cultural group. It is consisted of 256 distinct volumes we call odù and from them are established the dynamics of reflection and production of knowledge. By the word, by the sound, by the body and by the Yoruba world experiences it is how we approach the conceptual imaginary of Ifá, determining, however in general terms, the elements that identify the particular Yoruba epistemology that it is produced and also the producer of the language of Ifá system